PRINSIP-PRINSIP PENGELOLAAN BADAN HUKUM DI PT(KONTROVERSI SEPUTAR RUU BHP) - Hartini, Rahayu (Jurnal Bestari, 2008)
This warning observes the law aspects viewed from the principles of law institution management in the Plan of Law Regulation in Higher Education. The writing focuses on the topics of non profit organization, autonomy, non discrimination issues which become the main vision in the regulation.Related to the higher education rules, this writing points out on the importance of: having legal institution and the process of its formation, the relationship among the similar institutions, the difference between foundation?s legal institution and education? legal institution and the fund of the institution.